2006
DOI: 10.1016/j.febslet.2006.04.023
|View full text |Cite
|
Sign up to set email alerts
|

A kinase independent function for Tec kinase ITK in regulating antigen receptor induced serum response factor activation

Abstract: The Tec family kinases are critical downstream regulators of antigen receptor signals in lymphocytes. As kinases, they act on critical substrates to regulate signals such as calcium increase leading to activation of transcription factors such as NFAT, NFjB and SRF. We now show here that ITK, a member of the Tec family of tyrosine kinases, has a kinase independent function. Mutants of ITK that lack kinase activity or a kinase domain can rescue cells lacking Tec family kinases for antigen receptor induced SRF ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 34 publications
1
27
1
Order By: Relevance
“…We and others have also shown that certain functions of Itk are kinase-independent, including activation of the transcription factor SRF, modulating the localization of Vav GEF and induction of actin cytoskeleton rearrangements downstream of the TCR (14,16). However, our data indicate that Itk functions controlling the development of Th2-producing cells in vivo are kinase domain dependent.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…We and others have also shown that certain functions of Itk are kinase-independent, including activation of the transcription factor SRF, modulating the localization of Vav GEF and induction of actin cytoskeleton rearrangements downstream of the TCR (14,16). However, our data indicate that Itk functions controlling the development of Th2-producing cells in vivo are kinase domain dependent.…”
Section: Discussioncontrasting
confidence: 53%
“…We also generated mice carrying a kinase-deleted mutant of Itk either on a WT background (Tg(Lckpr-Itk⌬Kin)WT) or on an Itk null background (Tg(Lckpr-Itk⌬Kin)/Itk Ϫ/Ϫ ), which is expressed at ϳ25-30% of endogenous Itk. The Tg(Lckpr-Itk⌬Kin) was generated by cloning a mutant Itk with the kinase domain (Itk⌬Kin) replaced with enhanced GFP (14), into a transgenic expression cassette driven by the Lck proximal promoter and CD2 enhancer, which was a gift of Dr. A. Ray (University of Pittsburgh, Pittsburgh, PA) (23). All mice were backcrossed to C57BL/6 background for at least 10 generations.…”
Section: Micementioning
confidence: 99%
“…This interaction is not dependent on its kinase activity and could represent additional edges that emanate from the Itk signaling node. Indeed, kinase-deleted or kinase-inactive Itk have been shown to activate the transcription factor serum response factor or induce antigen-induced actin polarization in T cell lines (29,32,33). These data suggest that additional edges emanate from the Itk signaling node, independent of the edge leading to tyrosine phosphorylation of PLC-␥1.…”
Section: Cd8mentioning
confidence: 73%
“…Itk can regulate Vav localization and TCR-induced actin polarization independent of its kinase activity edge, but requires its PH and SH2 domains (29,33). In addition, the SH3 domain, but not kinase activity edge of Itk, is required for antigen receptor induced transcription factor SRF activation (32). This kinase domain independent edge can partially rescue antigen receptor induced activation of Erk in Tec kinase-null DT40 cells (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation